Strategic Leadership: Effective Leadership in Strategic Management - Suharto , Suharto (Sean Institute, 2023)
Strategic leadership is defined as the ability of a leader to direct an organization in achieving its strategic goals by utilizing resources optimally. This research aims to investigate the role of strategic leadership in the context of strategic management and its impact on organizational effectiveness. This research uses a qualitative approach with descriptive methods. The results of this research indicate that the implementation of strategic leadership has a significant positive impact on the organization's success in achieving long-term goals. Leaders who apply a strategic approach, with a deep understanding of the vision and mission, analysis of the business environment, and the ability to formulate innovative strategies, play a key role in guiding the team and creating clear direction. Leaders' flexibility and adaptability in facing changes in the business environment, along with intelligent strategic decision-making abilities, have been proven to make a positive contribution to organizational success. Performance monitoring and evaluation of strategy implementation results confirm that effective strategic leaders are able to create a work environment that supports innovation and empowers teams to achieve optimal results.